Kearifan Lokal Masyarakat Kelurahan Wolojita Sebagai Salah Satu Desa Penyangga dalam Upaya Konservasi Elang Flores di Taman Nasional Kelimutu - Stefan E. D. Atawatun; Maria M. E. Purnama; Fadlan Pramatana; Nixon Rammang (Wana Lestari, 2026)
This research was conducted in Wolojita Village, Ende Regency, East Nusa Tenggara Province, from February to March 2025. The aim of this study was to determine the local wisdom of the Wolojita community in Flores Hawk-eagle conservation efforts. The method used in this study was descriptive. Data were collected through interviews, direct observation, surveys, document analysis, and case studies. Purposive sampling was used to obtain relevant and accurate information and data from the field. The results of this study indicate that the local wisdom of the Wolojita community influences environmental conservation, particularly the Flores Hawk-eagle, so that it remains sustainable for future generations. The Joka Ju and Pati Ka Embu Mamo customs still apply today. During the Joka Ju ritual, residents are prohibited from engaging in activities outside the home. This is due to taboos that must be observed during this ritual. Violations of these taboos result in a customary fine (Poi) imposed by the traditional elders (Mosalaki). Another ritual is the pati ka embu mamo, which is performed to feed ancestors, summoning the Flores Eagle, an incarnation of the ancestor, to be fed. Kelimutu National Park involves the surrounding community in supporting the preservation of the Flores Eagle by assisting the Wolojita Village community, resulting in the formation of the Jata Bara Flores Eagle monitoring group, tasked with monitoring and ensuring the survival of the Flores Eagle.